2013
DOI: 10.2741/e658
|View full text |Cite
|
Sign up to set email alerts
|

Androgen insensitivity syndrome ten years of our experience

Abstract: Abnormalities of secondary sexual differentiation manifest in varying degrees depending upon the severity of the underlying cause. Primary amenorrhea in phenotypic females is caused by several different factors, including hormonal imbalance, nutritional deficiency and sex differentiation abnormalities. Androgen insensitivity syndrome (AIS) accounts for a large proportion of such cases in phenotypic females but genetically male individuals. Over the past 10 years, we have collected data related to androgen inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
2
3
0
1
Order By: Relevance
“…Such studies demonstrate that most patients with DSD 46, XY are initially registered as males. All patients with CAIS in our study were registered as females according to their phenotypes and this was confirmed in other researches ( 10 , 15 20 ).…”
Section: Discussionsupporting
confidence: 87%
“…Such studies demonstrate that most patients with DSD 46, XY are initially registered as males. All patients with CAIS in our study were registered as females according to their phenotypes and this was confirmed in other researches ( 10 , 15 20 ).…”
Section: Discussionsupporting
confidence: 87%
“…This difference may be due to more frequent consanguineous/endogamous marriages in India or the frequent occurrence of a hotspot SRD5A2 mutation (p.Arg246Gln) in the Indian population [Bittles, 2002;Arya et al, 2020]. Delayed presentation in Asian Indian patients is probably due to social inhibition and reluctance to seek medical attention [Subramaniam et al, 2013]. The male sex of rearing in PAIS patients with EMS ≥4 [Deeb et al, 2005] and rarity of gender dysphoria and gender role change in AIS (PAIS: 9%; CAIS: nil) were reproduced in our study [Mazur, 1963].…”
Section: Discussionmentioning
confidence: 99%
“…Unos pocos estudios retrospectivos han estimado que del 0.8 al 2.4% de las niñas con las hernias inguinales tienen síndrome de insensibilidad a los andrógenos 15 . Se han publicado casos de carácter familiar en los que algunos miembros muestran defectos mínimos en la virilización (microfalo o escroto bífido) y anomalías más severas, tales como: hipospadias perineoescrotal, ausencia de vasa deferens y orificio vaginal 16,17 . Un estudio de 150 casos 18 identificó mutaciones en el 39% de los pacientes y el establecimiento de la causa de la patogénesis en el 60% de ellos, con presentación tardía en la mayoría, y con poca concientización de los afectados y sus familiares.…”
Section: Discussionunclassified